MOBBING EFFECT JOB SATISFACTION - Abdukhalilov Rakhmatillo Haydaraliyevich (Research Focus International Scientific Journal, 2024)
The phenomenon of workplace mobbing, characterized by persistent bullying and harassment, has been identified as a significant factor influencing job satisfaction. This study aims to investigate the impact of mobbing on employees' job satisfaction levels, exploring the underlying mechanisms and potential moderating variables. Utilizing a cross-sectional survey design, data were collected from a diverse sample of employees across various industries. Statistical analyses, including regression and mediation models, were employed to assess the direct and indirect effects of mobbing on job satisfaction. The results indicate a strong negative correlation between mobbing and job satisfaction, with perceived organizational support and resilience emerging as significant moderating factors. These findings underscore the importance of addressing workplace mobbing to enhance employee well-being and organizational effectiveness.